Interstitial lung disease in mixed connective tissue disease - Marshell Tendean; Sazkia Aziza Nuriawan; Pringgodigdo Nugroho (Indonesian Journal of Rheumatology, 2017)
Interstitial lung diseases (ILD) are known as a debilitating pulmonary complications that may be occured in almost all systemic connective tissue diseases (CTD), including mixed connective tissue disease (MCTD). ILD is usually found in more than half of MCTD patients after 2-4years after the diagnosis made. A-47-years-old female initially diagnosed as systemic lupus erythematosus (SLE) developed a severe progressive dyspnea. She has recently diagnosed as MCTD with ILD after 9 months of initial symptoms. She was giving with Cyclophosphamide 500 mg IV pulse dose. However, after 1 months she developed severe pneumonia andpronounced demise due to intractable septic shock. The debilitating course of ILD is commonly seen in most systemic CTD. Therefore, it is important to perform initial screening and prevention. Systemic corticosteroid with or without immunosupressor agent(s) are indicated inILD-MCTD. Patients with progressive diseases will have poor prognosis.Keywords : ILD, MCTD, Corticosteroid